Processed Oesophageal Allografts For Hernioplasty In Pigs - Senthil Kumar S (Department of Surgery, College of Veterinary and Animal sciences, 2000)
The present study was conducted with the objectives of: 1. Evaluating the suitability of processed collagen based oesophageal allografts as a biological tissue substitute for hernioplasty in pigs and ii. Comparing the healing in herniorrhaphy and hernioplasty, in pigs. Twelve clinical cases of umbilical hernia in pigs of either sex, aged two to three months were used in the study. The animals were divided into two groups (Group I and Group Il) of six animals each based on the size of hernial ring. Group I animals were subjected to herniorrhaphy and Group Il animals were subjected to hernioplasty. Fresh pieces of oesophagus collected from slaughtered pigs were processed and cross-linked with gl u taraldehyde to prepare the graft. Triflupromazine hydrochloride was administered at the rate of 1.5 mgjkg body weight IjM to all the animals and local infiltration anaesthesia using lignocaine